Monkey tricks - Ashforth, Camilla (Walker London, 1992)
While his friend Horatio, a stuffed rabbit, enjoys the bungled tricks of a mischievous monkey, James, a teddy bear, wonders why the monkey's props look so familiar. Suggested level: preschool